MALE PATIENT WITH DISSECTION OF THE POSTERIOR CEREBRAL ARTERY AND OCULOMOTOR NERVE PALSY: A CASE REPORT AND A REVIEW FROM THE LITERATURE - Vojtikiv Samoilovska, Danijela; Arsovska, Anita; Kozlovska, Rodna; Trajkova, Suzana (Journal of Morphological Sciences, 2022)
Spontaneous intracranial artery dissection is an uncommon and probably under diagnosed cause of stroke and subarachnoid hemorrhage that is defined by the occurrence of a hematoma in the wall of an intracranial artery. We introduce a case of dissection of the P2 segment of the posterior cerebral artery (PCA) presented with new onset headache and unilateral, left oculomotor nerve palsy. The patient had a diagnosed thrombophilia and previous deep vein thrombosis. Digital subtraction angiography (DSA) revealed dissection of the P1-P2 segment of the PCA with occlusion of the distal branches P3-P4. CT excluded acute stroke. The patient was put on anticoagulant therapy, with clinical improving after 2 weeks. The left third nerve had been distorted because of vascular compression.  Conclusion: Isolated dissection of the PCA is rare. Multicenter prospective studies with standardized protocols for diagnosis, imaging, and follow-up of intracranial artery dissection are needed. Keywords: dissection, PCA